Organoleptic Acceptability And Antioxidant Activity Test On Yogurt With The Addition Of Telang Flower Extract - Okfrianti, Yenni; Wahyuni, Fepy; Wahyu, Tetes (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to determine the organoleptic acceptability and antioxidant activity of bay flower yoghurt with variations in the addition of bay flower extracts of 1%, 3%, and 5%. This research is important because functional foods such as synbiotic products that combine probiotics and prebiotics have significant health benefits. It is hoped that the results of the study will provide information on the optimal level of addition of telang flower extract in yogurt to obtain the best health benefits and good acceptance by consumers. Methodology: A one-factor completely randomized design was used in this study as the experimental method. The factor tested was the addition of bay flower extract with three treatment units: F1 (1%), F2 (3%), and F3 (5%). Data were collected through organoleptic tests on color, aroma, taste, viscosity, and overall by 30 panelists. In addition, antioxidant activity was measured using the DPPH method used to assess the ability of compounds to neutralize free radicals. Results: Organoleptic test results showed that 5% telang flower extract yogurt (F3) had the best acceptability. The antioxidant activity measurement results showed the total antioxidant activity of F1 was 909.88, F2 was IC50 750.8608, and F3 was IC50 1277.024. The antioxidant activity test results showed that the antioxidant strength was weak because the IC50 was more than 150. Findings: This study found that 5% bay flower extract yogurt (F3) had the best organoleptic acceptability. However, the antioxidant activity of bay flower yoghurt was still relatively weak despite the increase in bay flower extract addition. Novelty: This study offers a new approach in making bayang flower extract yoghurt as a source of anthocyanins and antioxidants. The use of telang flower in synbiotic yoghurt products is an innovation that has not been widely explored before. Originality: This study demonstrates originality in incorporating bay flower extract as a functional component in synbiotic yoghurt and evaluating its impact on organoleptic acceptability and antioxidant activity. Conclusion: This study concluded that 5% bay flower extract yoghurt (F3) was the best in terms of organoleptic acceptability, although its antioxidant activity was still weak. Paper Type: Research article.